How does context influence entrepreneurship education outcomes? Empirical evidence from Bangladesh and Germany. (1st August 2019) - Dickel, Petra; Kleemann, Linda; Bose, Tarun Kanti
This study uses quasi-experimental data from 245 students in Bangladesh and Germany to explore the effect of entrepreneurship education on entrepreneurial attitudes (perceived desirability and perceived feasibility) and entrepreneurial intentions. The study specifically focuses on how context factors influence entrepreneurship education outcomes. Difference-in-differences analysis with propensity score matching is used to control for selection bias. The results show that the perceived entrepreneurship environment significantly affects the impact of entrepreneurship education and that the strength and direction of effects differ between the two countries. The implications of these results for entrepreneurship research, educators and policy makers are discussed accordingly.